Findings of the 3-Month Supportive Treatment with Oncoxin Solution Beside the Standard Modalities of Patients with Different Neoplastic Diseases. - Uddin, Dayem; Islam, MA; Mahmood, I; Ghosh, AK; Khatun, RA; Kundu, S (TAJ: Journal of Teachers Association, 2009)
The incidence of Cancer is still increasing worldwide, specially, at an alarming rate in the developing countries and remain one of the major cause of morality worldwide. The role of different antioxidants, both in fruits and vegetable and in synthetic form as chemo-preventive measure is now well established from different studies. The incidence of cancer is lower in those countries where the traditional diet provides plenty of antioxidants. The aim of this study is to evaluate standard modalities of patients with different neoplastic diseases. Three identically designed, open and multi-centric studies were conducted at the same time in Bangladesh in 2008-2009. Efficacy of antioxidant rich product, Oncoxin, in head and throat, breast and uterine cervix cancer, when administered with conventional oncologic therapy Each study included 30 patient couples with similar stages of cancer. One patient of each couple received the standard treatment for their stage (reference group). The other (experimental group) also received Oncoxin for 365 days. The result gathered in the 3 studies showed that the administration of Oncoxin led to a significant improvement of the quality of life of patients, fewer episodes of depression and increased optimism. These patients handled better the radiotherapy and chemotherapy sessions with fewer and less intense adverse reactions. During the final visit, it was observed a 59.26% increase in the Karnofsky index in the experimental group compared to 30.38% in the reference group, and a 16.05% drop (76.93% due to deaths) in the experimental group for 39.24% (64.52% due to deaths) in the reference group. Survival rates were greater in the experimental group in all three studies (87.65% versus 74.68%). The treatment with ONCOXIN Solution proves its effectiveness as a treatment modality associated with complex oncological treatment, the short and medium terms. TAJ 2009; 22(1): 172-175